STUDI ANALISIS HIASAN SULAMAN BENANG PADA KAIN KATUN VALENTINO UNTUK BUSANA CASUAL WANITA (BUGARIS, 2024)
The background of the study are the fact of casual clothing display in many of variation of clothing ornament. The material used for making the casual clothing is valentino cotton which given threads embroidery ornament.The statement of the problem is "how good the results of casual clothing which have given the ornament of threads embroidery to valentine cotton in Surabaya. The purpose of the study is to describe the result of the ornament of threads embroidery to valentine cotton.Embroider is the form of art or craft decorate materials using the thread and the a diverse design. This research is descriptive quantitative which the data process used statistic procentage (%) data analysis technique. To collect the data the researcher used experimental, observation, and questionnaire. The sample of the research are 35 respondents which chose randomly and there are seven respondent who is expert in fashion The result of the study show that the making of casual fashion in valentine cotton which given threads embroidery ornament looks beautiful at procentage about 3,62 %. It means almost 90% respondent choose it. Therefore, the result of the study has the benefit as the references to develop the variation the ornament of threads embroidery. For the second, it used to references for the Family Prosperity Education Department of Fashion Designer in kerajinan dan rekayasa busana course as the references in University of PGRI Adi Buana Surabaya.